A preliminary checklist of the skippers (Rhopalocera: Hesperiidae) of Guangxi, China - Xue, Guo-Xi; Sun, Hao; Sun, Zhou; Wang, Shao-Neng (Zootaxa, 2016)
A survey of the literature shows that a total of 64 genera comprising 155 species/subspecies of skippers have been recorded in Guangxi. Based on a field survey and the examination of specimens, 1 subspecies, Burara gomata gomata (Moore, 1866), is recorded as new to China, and 1 species, Celaenorrhinus vietnamicus Devyatkin, 1998, is reported in Guangxi for the first time. Therefore, to date, a total of 57 genera with 109 species/subspecies in 4 subfamilies of Hesperiidae have been positively identified as the fauna of Guangxi. Four genera and 42 species/subspecies are considered as requiring confirmation, and 3 genera and 6 species/subspecies are excluded. Some taxonomic notes are provided when necessary.